Efficacy of fungicides in management of Downy mildew disease of Cucumber (Cucumis sativus L.) under open field conditions, in Dhading district of Nepal - Pandit, Shailesh; Manandhar, Hira Kaji; Dhakal, Krishna Hari; Rijal, Sramika; Bhandari, Sandesh; Paneru, Sushma (Journal of Agriculture and Natural Resources, 2020)
Downy mildew (Pseudoperonospora cubensis) is one of the most important disease of cucumber under open field conditions. Hence, the experiment was conducted to study the efficacy of fungicides in management of downy mildew disease of cucumber (Cucumis sativus L.) under open field in Chauradi-7 Dhading during spring season, 2019. Bhaktapur local variety of cucumber was used for the study. The experiment was laid out in single factor randomized complete block design with four replications. Three different bio-fungicides; Trichoderma viride + Trichoderma harzianum, Bacillus subtilis, Verticillium lecanii and one chemical fungicide; Krilaxyl (metalaxyl 8% + mancozeb 64%) were used as treatments. Normal water spray served as control. It was observed that bio-fungicides had insignificant effect in controlling the downy mildew. Pathological observation such as disease incidence percentage, severity percentage and AUDPC in bio-fungicides treated plots were not significantly different from water-sprayed control plots. Similarly, biometric attributes such as number of fruit, length and diameter of fruit, weight of fruit were also non-significant. Krilaxyl resulted significant effect in controlling downy mildew, providing maximum disease reduction (37.48%-50.72%) with lowest disease incidence (1.25-61.25%) and lowest value of AUDPC (138.7). Krilaxyl treated plots had higher number of fruit (6), longer length of fruit (17.15-18.95), higher diameter of fruit (4.16- 4.45 cm) and higher weight of fruit (677 - 759 g). Hence, chemical fungicide Krilaxyl was found better for the management of downy mildew disease in open field cucumber cultivation. Further, researches on bio-fungicides, especially of native strains are required for best result.